Unlocking the digital organization : a view of the digital transformation capabilities - Leso, Bernardo Henrique (2022)
Digital transformation is a complex process enabled by the application of digital technologies that fundamentally change the business model of organizations, altering their ways of capturing and generating value, their organizational processes, routines, sources of revenue, and resources. It is such a pressing phenomenon in the current context (accentuated by the COVID-19 pandemic) that all organizations will be impacted and will have to deal with it sooner or later. Thus, to understand the mechanisms that assist organizations in creating strategic conditions for successful transformations, this thesis focuses on the phenomenon and seeks a deep understanding of the elements that compose it. Through a comprehensive and robust work that mixes qualitative methods (such as systematic review and multiple case studies) with quantitative methods (such as EFA and PLS), the thesis presents significant and impactful results. Among them are (i) the proposition of a Digital Transformation Dynamic Capability framework and (ii) a subsequent capability-based maturity model, and (iii) the proposition of a model (statistically tested in SMEs) about the framework's antecedent factors. A distinct point of this theoretical proposition is the use of dynamic capabilities lens for the framework organization - allowing the understanding of the phenomenon as a process to be continuously pursued. Thus, the main contributions lie in a comprehensive and original approach that can guide organizations to articulate and develop the conditions to unlock the capability to digitally transform their business model - which can lead to a capacity for continuous change in the digital context. Furthermore, it offers robust and timely research whose models condense a knowledge corpus from which future research can benefit.